MODIFICATION OF IRON OXIDE CATALYSTS SUPPORTED ON THE BIOMASS BASED ACTIVATED CARBON FOR DEGRADATION OF DYE WASTEWATER (Jurnal Bahan Alam Terbarukan, 2018)
Methylene blue is one of the dyes in textile industries which has a negative impact on the environment. This compound is very stable, so it is difficult to degrade naturally. Methylene blue can be harmful to the environment if it is in a very large concentration, because it can increase the value of Chemical Oxygen Demand (COD) which can damage the balance of environment ecosystem. Adsorption method by using activated carbon as the adsorbent is one of the most efficient and effective techniques in dye removal due to its large adsorption capacity. However, the adsorption method using activated carbon only removes the pollutant compounds to other media or phases. Other method that can be used includes Advanced Oxidation Processes (AOPs). This method has the advantage of being able to degrade harmful compounds in the waste through oxidation (oxidative degradation) processes. One method of AOPs is the process by using Fenton reagents. This study was aimed to prepare and characterize iron oxide/porous activated carbon catalyst. The type of porous activated carbon used was carbon from biomass derived carbon with microporous character. This biomass carbon is obtained from renewable natural products, namely coconut shell.The kinetics and adsorption models in the material will be derived and evaluated from the research data. Based on the research, it can be concluded that catalytic degradation is very effective for degradation of dye wastewater. Methylene blue degradation increases with the use of Fe2O3/activated carbon catalyst and the addition of hydrogen peroxide as the Fenton reagent. In addition, the pore structure difference in the catalyst also had a significant effect on the methylene blue degradation reaction resulting in increased capacity of methylene blue degradation reactions.